2016
DOI: 10.1111/aor.12830
|View full text |Cite
|
Sign up to set email alerts
|

Hemodiafiltration—A Technique for Physiological Correction of Priming Solution in Pediatric Cardiac Surgery: An In Vitro Study

Abstract: Pediatric cardiopulmonary bypass (CPB) circuit invariably requires priming with packed red blood cells (PRBCs). Metabolic composition of stored PRBCs is unphysiological and becomes worse with increasing duration of storage. It is recommended to correct these abnormalities before initiation of CPB. We tested the hypothesis that hemodiafiltration of the prime with 0.45% saline is sufficient for reducing the metabolic load and reaching a physiologic state. In an in vitro study, 100 mL of blood each from 45 units … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0
3

Year Published

2018
2018
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(11 citation statements)
references
References 17 publications
(33 reference statements)
0
8
0
3
Order By: Relevance
“…However, massive transfusions given quickly at the beginning of CPB may overwhelm the capacity of the liver. In addition, hypothermia and depressed hepatic functions may increase citrate toxicity . In our study, we demonstrated that the Z‐BUF of the priming blood diminished lactate as a weak acid in the priming blood: the level of lactate was significantly lower in the Z‐BUF group than in the control group at admission to the ICU.…”
Section: Discussionmentioning
confidence: 56%
See 4 more Smart Citations
“…However, massive transfusions given quickly at the beginning of CPB may overwhelm the capacity of the liver. In addition, hypothermia and depressed hepatic functions may increase citrate toxicity . In our study, we demonstrated that the Z‐BUF of the priming blood diminished lactate as a weak acid in the priming blood: the level of lactate was significantly lower in the Z‐BUF group than in the control group at admission to the ICU.…”
Section: Discussionmentioning
confidence: 56%
“…Rapid and massive transfusions of the priming blood may lead to hyperkalemia, cardiac arrhythmias, and cardiac arrest and acute hypernatremia‐induced brain shrinkage may result in intracranial hemorrhage and venous thrombosis . We performed Z‐BUF on the priming blood by using 0.45% sodium chloride and observed improvement in the levels of potassium, sodium, and chlorine.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations